(untitled) (Journal of Pharmaceutical Negative Results, 2023)
A pot culture experiment entitled “Impact of inorganic nitrogenous fertilizers and farmyard manure combination on nitrogen content by grain, straw at harvest and protein content of grain in ppm” was conducted at the Institute of Agricultural Sciences farm, Sikha ‘O’ Anusandhan (Deemed to be University), Bhubaneswar Odisha. on sandy loam soil during Kharif 2018-2019. Eight treatments made up the experiment: T1- (Control), T2 - 50% RDF, T3-50% RDF + FYM @ 5 t ha-1, T4- 75% RDF, T5-75% RDF + FYM 5t ha-1, T6- 100% RDF (NPK 80:40:40), T7-100% RDF + FYM 5t ha-1, T8-150% RDF. Three replications of the experiment were set up using a Randomized Block Design. The findings showed that the treatment that received 100% RDF + FYM @ 5t ha-1 recorded the highest and most significant values for growth parameters, such as plant height, number of tillers per hill, effective tillers per hill, and yield attributes, such as number of panicles per hill, panicle length, and the number of filled grains 1000 seed weight (test weight). In addition, larger increases in the aforementioned parameters were seen when FYM (5t ha-1) was combined with lower amounts of RDF (50 and 75% RDF), as opposed to the application of inorganic fertilizers alone at the corresponding levels. The trend in grain and straw yields was similar to that of the growth parameters, and at higher concentrations of nitrogen in the inorganic form (150% RDF), the values of all of the parameters, including grain and straw yield, were significantly lower than in the treatment where 100% RDF + FYM 5t ha-1 was used. The application of 100% RDF + FYM 5t ha-1 increased the number of nutrients (N, P, and K) in grain and straw compared to 100 and 150% RDF. With the combined application of 100% RDF as an inorganic source and 5 t ha-1 FYM as an organic source, improvements in physicochemical parameters such as organic carbon, bulk density, porosity, and accessible macronutrients (N, P,K) were seen. Based on the results of the investigation, it can be said that inorganic nitrogen applied to sandy loam soils in Odisha at 100% RDF level along with FYM 5 t ha-1 improved physical conditions and the availability of macronutrients. Higher levels of RDF (150%) produced yields that were significantly lower than those produced by the combination of inorganic and FYM and yields that were nearly equal to those produced with the recommended dose of nitrogen (100% RDF) only in mineral form.